Hands-on serverless computing : build, run and orchestrate serverless applications using AWS Lambda, Microsoft Azure functions, and Google cloud functions /: build, run and orchestrate serverless applications using AWS Lambda, Microsoft Azure functions, and Google cloud functions. (2018) - Chowhan, Kuldeep
No abstract available